Empowering extension managers through Participatory learning approach - G. Jaya; M.N. Reddy (Journal of Agricultural Extension Management, 2025)
Organizational effectiveness depends largely on the people in the organization. Human resources are organic and complex and so is their development. While education is an instrument for the general development of the individual and his faculties, Human Resource Development in the context of an organization refers to the improvements in the capacities and capabilities of the personnel in relation to the needs of the organization. It creates a climate in which the flower of human knowledge, skills, capabilities and creativity can bloom. It involves the use of processes through which the personnel in organizations get prepared to give their best to meet the organization's objectives and achieve optimal effectiveness in their job roles. It sets up systems through which human capabilities and potential can be identified and tapped to the mutual satisfaction of the individual and organization